QCA TECHNOLOGY FOR IMPLEMENTATION OF CRYPTOGRAPHY ENGINEERING - Melnik, O. S.; Sverdlova, A. D. (Science-based technologies, 2015)
Since the introduction of side-channel attacks, cryptographic devices have been highly susceptible to power and electromagnetic (EM) analysis attacks; because these attacks require only relatively inexpensive equipments. Unless adequate countermeasures are implemented, side channel attacks allow an unauthorized person to reveal the private key of a cryptographic module. Countermeasure a novel logic approach to Quantum-dot Cellular Automata (QCA). The proposed logic takes advantage of low power consumption QCA together with complicated clocking circuits as a paradigm of nanotechnology advances in cryptography engineering.